Spotkanie przy mediacyjnym stole. Konteksty pedagogiczne - Janeczko-Janicka , Maria (Studia Edukacyjne, 2023)
The aim of this paper is to analyze the potential connected with using mediation as an educational method. The role of technology in contemporary society is constantly growing. The COVID-19 pandemic makes us aware of how elementary and fundamental presence is. Encounter as a pedagogical category shows many dimensions and educational benefits. Peer mediation offers a constructive approach to peer conflict, resolving it through meeting and conversation in the presence of an impartial and neutral mediator (school peer). A mediation session teaches responsibility for the decisions taken and creates a sense of agency. Mediation is conducive to the development of key competences in the postmodern world.